Spontaneous Subcapsular Hematoma of the Fetal Liver: A Case Report and Review of Literature - James E. Maher; Brittany Van Beek; Randall T. Kelly; Peter Hsu (Thieme Medical Publishers, Inc., 2015)
Abstract We report a case of a cystic abdominal mass on ultrasound which presented a diagnostic dilemma at 32 weeks gestation. A presumptive antenatal diagnosis of a subcapsular liver hematoma (SCH) was made based on the location and ultrasound appearance similar to SCH seen in pediatric and adult patients. Sequential evaluation of the mass showed an evolving ultrasound appearance which reinforced our initial impression of a subcapsular hematoma of the fetal liver. Postnatal ultrasound confirmed the resolving SCH as well as a previously undetected echo bright lesion characteristic of an infantile focal hemangioma directly adjacent to the resolving SCH. A review of the literature is provided.